Uganda Economic Update, 11th Edition, May 2018 : Financing Growth and Development - Options for Raising More Domestic Revenues - World Bank Group (World Bank, Washington, DC, 2018)
Uganda's fiscal policy has remained mainly expenditure driven, with domestic revenue continuing to lag. This has resulted in a widening financing gap. In the 10-year period to 2017, the total valueof public expenditure increased from 15 percent of GDP to more than 20 percent. During this time, the tax-to-GDP ratio grew by an average annual rate of 0.2 percentage points, with the value of collected revenues increasing from 10 to 13.8 percent of GDP over the same period. By 2016, the value of Uganda's collected per capita revenues stood at US$ 211 of PPP adjusted to 2011 international dollars. This covered 66 percent of general government expenditures, with the remainder covered by loans and grants. The gap between revenues and expenditures could continue to increase into the future, with the expenditure increasing to meet the need to develop thestock of physical infrastructure and to raise the quality and quantity of social services to meet the needs of Uganda’s rapidly expanding population.